1998
DOI: 10.1007/s002619900318
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial cysts of the pancreas: CT and sonographic findings

Abstract: Two cases of rare lymphoepithelial cyst (LEC) of the pancreas are presented. Although the histogenesis of this lesion is not known, it can be histologically differentiated from other pancreatic and retropancreatic cysts. The importance of its recognition is in the distinction from cystic neoplasm of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…This finding is similar to those reported in previous reports (6,8,9). Radiologists should be aware of this contradictory finding, in order to narrow the differential diagnosis when a cystic lesion of the pancreas is present.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is similar to those reported in previous reports (6,8,9). Radiologists should be aware of this contradictory finding, in order to narrow the differential diagnosis when a cystic lesion of the pancreas is present.…”
Section: Discussionsupporting
confidence: 79%
“…The attenuation values of the internal contents sometimes exhibit negative Hounsfield units, implying the presence of lipid contents (6,8). It has been suggested that a combination of a cystic appearance on CT and a nonhomogeneous echogenicity on sonography can provide a clue to the correct diagnosis (6,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe that this marker has no utility in the clinical assessment of these cystic lesions [14] . Consistent with published reports [15] , CECT scans in our patients demonstrated cysts with thin walls, without evidence of calcificystic lesions. Seventy-one percent of cysts in a recent report from our institution were serendipitous imaging findings [4] .…”
supporting
confidence: 93%
“…Of the reported cases, 80% involved patients aged over 40 years. 7,8 Some patients are asymptomatic, and the lesions are found incidentally during abdominal US or CT. Other patients have an isolated symptom such as abdominal pain, or a combination of symptoms including nausea, vomiting, diarrhea, fever, weight loss, and fatigue. Sako et al 9 reported that LECs causing symptoms are greater than 3 cm in diameter, whereas those that cause no symptoms are less than 6 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%